Teenage pregnancy, romantic love and social science - an uneasy relationship - FINLAY, ANDREW ROBERT (Blackwell, 1996)
This chapter re-examines health services research on teenage pregnancy in the light of recent work in the sociology of emotion. I was prompted to write it because, having recently coordinated a study of teenage pregnancy, I had become increasingly uneasy with a pivotal dichotomy around which much of this research turns; namely that between planned and unplanned pregnancy . The study had a number of elements, but the main one consisted of semi-structured interviews with 62 pregnant teenagers. My unease with the dichotomy between planned and unplanned pregnancy arose from the suspicion that these were not truly `emic? categories for most respondents. Although they understood the terms, respondents would probably not have used them had the interviewer not introduced them. It is possible that the dichotomy may obscure important aspects of the experience of being young, single and pregnant, particularly the emotional aspect.
PUBLISHED
Keywords: medicine and psychology; teenage pregnancy; social medicine